Effect of Microstructure on Corrosion Behavior of WE43 Magnesium Alloy in As Cast and Heat-Treated Conditions - Chenxi Yang; Nikhil Gupta; Hanlin Ding; Chongchen Xiang (Metals, 2020)
The improvement in corrosion resistance of WE43 was well realized by heat treatment. To study the influence of microstructure on the corrosion behavior of WE43 in as-cast and heat-treated conditions, an immersion test was employed with as-cast and heat-treated samples in the 3.5% NaCl solution. The corrosion rate and change of morphology were recorded and the corrosion behavior was further investigated by scanning electron microscopy (SEM). The results indicated that the corrosion rate of the WE43 alloy decreased after heat treatment. It was observed that the eutectic gradually damages the protective film on the surface of the as-cast WE43 in the process of corrosion, which further increases the corrosion rate. The Zr-rich phase formed a domed structure resulting in the adjacent area being further corroded. The Y-rich phase has little effect on the corrosion reaction.